2021
DOI: 10.3390/medicina57020168
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death in Athletes: From the Basics to the Practical Work-Up

Abstract: Sudden cardiac death in athletes is a relatively rare event, but due to the increasing number of individuals practicing high-performance sports, in absolute terms, it has become an important issue to be addressed. Since etiologies are many and the occurrence is rare, tracing the ideal preparticipation screening program is challenging. So far, as screening tools, a comprehensive clinical evaluation and a simple 12-lead electrocardiogram (ECG) seem to be the most cost-effective strategy. Recent technological adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
0
13
0
1
Order By: Relevance
“…Niektóre szacunki obejmują tylko zgony w czasie wysiłku lub wkrótce po jego zakończeniu (po upływie poniżej 1 godziny), a inne każdy SCD u sportowca (wysiłkowy i poza wysiłkiem), a także przypadki nagłego zatrzymania krążenia niezakończone zgonem. Również definicja sportowca w badaniach epidemiologicznych oceniających incydenty sercowe nie jest jednolita [2,3]. Wiarygodne dane pochodzą z badań przeprowadzonych we Włoszech, w regionie Veneto, z wykorzystaniem danych z regionalnych rejestrów.…”
Section: Epidemiologia I Czynniki Ryzykaunclassified
“…Niektóre szacunki obejmują tylko zgony w czasie wysiłku lub wkrótce po jego zakończeniu (po upływie poniżej 1 godziny), a inne każdy SCD u sportowca (wysiłkowy i poza wysiłkiem), a także przypadki nagłego zatrzymania krążenia niezakończone zgonem. Również definicja sportowca w badaniach epidemiologicznych oceniających incydenty sercowe nie jest jednolita [2,3]. Wiarygodne dane pochodzą z badań przeprowadzonych we Włoszech, w regionie Veneto, z wykorzystaniem danych z regionalnych rejestrów.…”
Section: Epidemiologia I Czynniki Ryzykaunclassified
“…Magnesium is demonstrated to promote muscle synthesis through activation of the mTOR pathway [106]. Magnesium might have a lifesaving role in sports due to its demonstrated arrhythmia prevention effects [131], given that most sudden cardiac deaths in athletes occur through arrhythmias [132]. Multiple studies have proved the efficiency of magnesium in sports-related performance, such as increases in muscle strength and walking and running speed and a decrease in lactate levels [105].…”
Section: Mineralsmentioning
confidence: 99%
“…Hypertrophic cardiomyopathy (HCM) is a genetic disease of the sarcomere characterized by abnormal left ventricular (LV) hypertrophy [ 1 ]. Previous studies have reported that HCM is one of the most common heart diseases in patients with sudden cardiac death (SCD) [ 2 ]. SCD due to ventricular tachycardia (VT) is the most devastating consequence of HCM [ 3 ].…”
Section: Introductionmentioning
confidence: 99%